AMPK activation induced in pemetrexed‐treated cells is associated with development of drug resistance independently of target enzyme expression. Issue 6 (15th May 2019) - Qin, Yiyang; Sekine, Ikuo; Hanazono, Michiko; Morinaga, Takao; Fan, Mengmeng; Takiguchi, Yuichi; Tada, Yuji; Shingyoji, Masato; Yamaguchi, Naoto; Tagawa, Masatoshi
Abstract : Pemetrexed (PEM) inhibits DNA and RNA synthesis and is currently one of the first‐line agents for mesothelioma. PEM suppresses the activities of several enzymes involved in purine and pyrimidine synthesis, and elevated activity of these enzymes in tumors is often linked with resistance to PEM. The agent also stimulates AMP‐activated protein kinase (AMPK) and consequently influences the mammalian target of rapamycin complex 1 (mTORC1) pathways. Nevertheless, it remains unclear whether PEM resistance is linked to the AMPK or mTORC1 pathways. Here, we established two independent PEM‐resistant mesothelioma cell lines in which expression of the PEM‐target enzymes was not elevated, and found that levels of phosphorylated AMPK and p70S6K and, to a lesser extent, levels of phosphorylated AKT and p53, were increased in these cells as compared with the respective parent cells. PEM stimulation also augmented phosphorylation of AMPK, p70S6K, AKT and p53 in most cases. An AMPK activator increased phosphorylation and PEM resistance in parental cells, and the inhibitor decreased the resistance of PEM‐resistant cells. In contrast, inhibitors for p70S6K and AKT did not influence PEM resistance; furthermore, increased levels of endogenous p53 did not affect PEM sensitivity. These data collectively indicate that constitutive activation of AMPK is associated with PEM resistance, and that this is unconnected with elevated DNA and RNA synthesis. Abstract : Pemetrexed (PEM), an anti‐cancer agent, inhibits the activity of enzymes involved in DNA/RNA synthesis and AICART. Suppressed AICART activity increases the substrate, ZMP, an AMP analog, and consequently augments AMPK function, which in turn influences mTORC1 responses. The current study showed that PEM‐resistant mesothelioma exhibited constitutively activated AMPK and that the increased AMPK activity was linked with PEM‐resistance, which was unconnected to DNA/RNA synthetic enzymes.